Cholinergic Potentiation Alters Perceptual Eye Dominance Plasticity Induced by a Few Hours of Monocular Patching in Adults - Sheynin, Yasha; Chamoun, Mira; Baldwin, Alex S.; Rosa-Neto, Pedro; Hess, Robert F.; Vaucher, Elvire (Frontiers in Neuroscience, 2019)
A few hours of monocular deprivation with a diffuser eye patch temporarily strengthens the contribution of the deprived eye to binocular vision. This shift in favour of the deprived eye is characterized as a form of adult visual plasticity. Studies in animal and human models suggest that neuromodulators can enhance adult brain plasticity in general. Specifically, acetylcholine has been shown to improve certain aspects of visual function and plasticity in adulthood. We investigated whether a single administration of donepezil (a cholinesterase inhibitor) could further augment the temporary shift in perceptual eye dominance that occurs after two hours of monocular patching. Twelve healthy adults completed two experimental sessions while taking either donepezil (5 mg, oral) or a placebo (lactose) pill. We measured perceptual eye dominance using a binocular phase combination task before and after two hours of monocular deprivation with a diffuser eye patch. Participants in both groups demonstrated a significant shift in favour of the patched eye after monocular deprivation, however our results indicate that donepezil significantly reduces the magnitude and duration of the shift. We also investigated the possibility that donepezil reduces the amount of time needed to observe a shift in perceptual eye dominance relative to placebo control. For this experiment, seven subjects completed two sessions where we reduced the duration of deprivation to one hour. Donepezil reduces the magnitude and duration of the patching-induced shift in perceptual eye dominance in this experiment as well. To verify whether the effects we observed using the binocular phase combination task were also observable in a different measure of sensory eye dominance, six subjects completed an identical experiment using a binocular rivalry task. These results also indicate that cholinergic enhancement impedes the shift that results from short-term deprivation. In summary, our study demonstrates that enhanced cholinergic potentiation interferes with the consolidation of the perceptual eye dominance plasticity induced by several hours of monocular deprivation.